Uji Fitokimia Ekstrak n-Heksana Daun Belimbing Wuluh (Averrhoa bilimbi L.) - Reni Tri Febriyanti; Haeruddin; La Rudi (Sains: Jurnal Kimia dan Pendidikan Kimia, 2022)
Research has been carried out "Phytochemical Test and Antioxidant Activity of n-Hexane Extract of Belimbing Wuluh Leaves (Averrhoa bilimbi L.)". This study aims to determine the class of secondary metabolites contained in starfruit leaves (Averrhoa bilimbi L.) which were extracted using n-hexane as solvent and to determine the antioxidant activity of starfruit leaves (Averrhoa bilimbi L.) which were extracted using n-hexane as solvent. The secondary metabolite compounds contained in starfruit leaves (Averrhoa bilimbi L.) were determined by the phytochemical method, while the antioxidant activity was determined by the 2,2-Diphenyl-1-Picrylhydrazine (DPPH) method. This study began with sample extraction using the soxhletation method, respectively 15 and 20 g of dried and mashed star fruit leaves, then soxhelated for 3-4 hours with n-hexane as solvent. The extraction was carried out for 7 repetitions so that the total sample of starfruit leaves extracted was 110 g. The extract resulting from soxhletation was then collected and concentrated to obtain a thick extract. The viscous extract obtained was then subjected to phytochemical tests and DPPH tests. Phytochemical test results showed that starfruit leaves extracted using n-hexane as solvent by soxhletation method only contained steroids. Starfruit leaf extract which was extracted using n-hexane solvent by soxhletation method had very weak antioxidant activity with an IC50 value of 3,229,213 ppm.